Expanding the Arsenal of FGFR Inhibitors: A Novel Chloroacetamide Derivative as a New Irreversible Agent With Anti-proliferative Activity Against FGFR1-Amplified Lung Cancer Cell Lines - Fumarola, Claudia; Bozza, Nicole; Castelli, Riccardo; Ferlenghi, Francesca; Marseglia, Giuseppe; Lodola, Alessio; Bonelli, Mara; La Monica, Silvia; Cretella, Daniele; Alfieri, Roberta; Minari, Roberta; Galetti, Maricla; et al. (Frontiers in Oncology, 2019)
Fibroblast Growth Factor Receptors (FGFR1−4) have a critical role in the progression of several human cancers, including Squamous Non-Small-Cell Lung Cancer (SQCLC). Both non-selective and selective reversible FGFR inhibitors are under clinical investigation for the treatment of patients with tumors harboring FGFR alterations. Despite their potential efficacy, the clinic development of these drugs has encountered several challenges, including toxicity and the appearance of drug resistance. Recent efforts have been directed at development of irreversible FGFR inhibitors, which have the potential to exert superior anti-proliferative activity in tumors carrying FGFR alterations. With this in mind, we synthetized and investigated a set of novel inhibitors possessing a warhead potentially able to covalently bind a cysteine in the P-loop of FGFR. Among them, the chloroacetamide UPR1376 resulted able to irreversible inhibit FGFR1 phosphorylation in FGFR1 over-expressing cells generated from SQCLC SKMES-1 cells. In addition, this compound inhibited cell proliferation in FGFR1-amplified H1581 cells with a potency higher than the reversible inhibitor BGJ398 (infigratinib), while sparing FGFR1 low-expressing cells. The anti-proliferative effects of UPR1376 were demonstrated in both 2D and 3D systems and were associated with the inhibition of MAPK and AKT/mTOR signaling pathways. UPR1376 inhibited cell proliferation also in two BGJ398-resistant cell clones generated from H1581 by chronic exposure to BGJ398, although at concentrations higher than those effective in the parental cells, likely due to the persistent activation of the MAPK pathway associated to NRAS amplification. Combined blockade of FGFR1 and MAPK signaling, by UPR1376 and trametinib respectively, significantly enhanced the efficacy of UPR1376, providing a means of circumventing resistance to FGFR1 inhibition. Our findings suggest that the insertion of a chloroacetamide warhead on a suitable scaffold, as exemplified by UPR1376, is a valuable strategy to develop a novel generation of FGFR inhibitors for the treatment of SQCLC patients with FGFR alterations.